Prediction model investigations of the reinforced fine-grained tailings dam overtopping failure - Chen, Meibao; Jing, Xiaofei; Xie, Dongxu; Li, Xiaoshuang; Zhang, Yuanzhen; Liu, Xiaohua (Frontiers in Earth Science, 2023)
Overtopping dam break is a frequent accident in tailings reservoirs. However, little attention has been paid to the study of overtopping hydraulic erosion damage characteristics of tailings dam after adding reinforcement. Nowadays, there were few people have researched the prediction of the overtopping failure process of the reinforced tailings dam. It is important significance to establish a prediction model for the overtopping of reinforced tailings dam which aims at the problem of overtopping erosion of reinforced tailings. For the anti-erosion and anti-collapse effects of the reinforced tailings dam, a mathematical model for the development of the overtopping breach of the reinforced tailings dam is established. The formula of reinforced erosion rate derived from water flow shear stress theory, simulation of breach erosion development by time iteration method in the mathematical model. Secondly, the limit equilibrium method is used to analyze the stability of the reinforced breach slope. Then, the physical test is used to reproduce the dam failure process of the tailings dam. In addition, the development process of the breach and discharge are monitored. Ultimately, the maximum depth and width of the breach are in brilliant agreement with the calculated values.